KELAYAKAN INVESTASI SPKLU ULTRA FAST CHARGING BAKAUHENI-TERBANGGI - Eri Prabowo; Trassanda Scudetto Widestomo Putra; Shafia Ananda (entries, 2026)
This study evaluates the financial feasibility and risk sensitivity of constructing two 100 kW ultra-fast charging stations for electric vehicles (EVs) along the Bakauheni-Terbanggi Besar Toll Road corridor. This assessment is crucial because the transition to electric vehicles in Indonesia requires reliable charging infrastructure along intercity travel corridors, whereas ultra-fast charging facilities in Sumatra remain limited. The study employs a descriptive quantitative approach using secondary data, including traffic reports, PLN tariff references, BPS (Statistics Indonesia) data, and EV projections. Analysis was conducted using Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period, alongside sensitivity scenarios based on charger occupancy rates and electricity tariffs. The initial investment is estimated at IDR 2.167 billion. A pessimistic scenario involving 12 vehicles per day yielded an IRR of 6.33% and a payback period of 6.73 years, rendering it financially unattractive. Moderate and optimistic scenarios resulted in IRRs of 16.14% and 34.81%, respectively. The findings indicate that the project is feasible under moderate and optimistic conditions but requires phased development, operational risk mitigation, and tariff risk management.